Making linear multimedia interactive: questions, solutions and types of reflection. (14th December 2020) - Lebedev, Petr; Lindstrøm, Christine; Sharma, Manjula Devi
Abstract: Typically, the format of online physics educational videos is closer in style to direct instruction rather than being interactive. One simple way of making videos more interactive is asking questions in one video, providing solutions in the second and seeking student reflection. This study utilises two physics education videos by Derek Muller (Veritasium) which were deployed with 508 first year physics students at The University of Sydney. The students watched the first video, which asked four physics questions, and were prompted to write down their answers. After this, the students were shown the solutions video and asked whether they changed, or did not change their answer, and their reasons for doing so. Data were analysed with a mixed-methods approach. While students whose answers did not match the solutions mostly modified their answers, a nontrivial percentage did not. An interesting finding is that the reasons provided for modifying or not modifying their answers are similar, or 'mirrors' of each other. We comment on the nature of the questions and the opportunities for learning by incorporating reflective thinking, particularly through videos that use a question, solution & reflection style.